APLIKASI METODE IRIDOLOGI UNTUK IDENTIFIKASI STRES PADA SISWA SD, SMP DAN SMA MENGHADAPI UJIAN NASIONAL (UN) DI SUMATERA BARAT - Abdul Razak (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
The research on the application of the method Iridologi on education for the identification of stress on the elementary, junior high and high school in West Sumatra have been implemented since 2009-2011. This study aims to determine the effectiveness of methods for identification of stress Iridologi students in teaching and learning to follow the National Examination in elementary, middle and high school. So far, education experts do not have a physical examination methods stress levels of students in learning process for success in National Examination (UN). With Iridologi methods (physical examination of the iris) is easy to determine the level of stress to find a solution. Iridologi is a branch of science neurology (the science of nerves). Iridologi able to detect changes in body condition which is reflected by a smooth peripheral nerves throughout the body in humans and vertebrate animals. This study is a pioneering application of biology to solve problems in education. The subjects studied were students at 6 SMAN in 3 districts (Padang City, Sijunjung and Pesisir Selatan regency), SDN 38 students in the city of Padang and students in the district Sijunjung SMPN 9. The results in 2009 at the stress level high school students facing the UN in 2010 was 68% and levels of stress were 32% rate of severe stress. Subsequently, in 2010, for elementary students, 0.08% tingat mild stress, the stress level is 65.7% and 24.3% rate of severe stress. In 2011, for junior high school students found a mild 0.8% stress levels, stress levels were 59% and 32% stress level. Conclusion from three years study showed that the method Iridologi effectively demonstrated Iridologi stress levels of students from elementary, middle and high school students to follow the national examination (UN).Kata kunci: Metode Iridologi, Identifikasi Stres